Research on the Localization Marketing Strategy of Multinational Catering Enterprises in Overseas: A Case Study of KFC - Chen, Yumeng (Transactions on Social Science, Education and Humanities Research, 2024)
Taking KFC as an example, this study discusses the localization marketing strategy of multinational catering enterprises in the host country. In the context of economic globalization, multinational companies are faced with various challenges such as culture, language and social consciousness, and localization strategy has become an important means to adapt to these differences. By analyzing the marketing strategies of KFC in China, Japan and other markets, this study reveals the key factors of its success. The study found that KFC’s success in the Chinese market and other countries cannot be separated from its popular localization strategy. This study will use SWOT method for argumentation and analysis. The research in this study not only reveals the successful operation experience of KFC, but also reveals the shortcomings of other multinational catering companies, such as Starbucks, in the localization marketing. In addition, it also provides a useful reference for other multinational catering enterprises in the localization of marketing, but also provides valuable experience for multinational companies in other industries.